2022
DOI: 10.1049/cmu2.12439
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge engineering–based DApp using blockchain technology for protract medical certificates privacy

Abstract: In the Industry 4.0 era, an inherited featured technology, blockchain, plays a vital role in knowledge engineering applications. Blockchain provides privacy to sensitive data as an intelligent agent, so its adoption rate increases in all the advanced domains. Especially in the health care department, blockchain technology usage helps avoid attacks like the Wannacry ransomware attack during 2017. Therefore, this paper described a decentralised application (DApp) expert system using public blockchain to create a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The Table 2 shows that the sturdiness of the offered process is higher than the algorithms against several signal processing attacks mentioned by previous researchers. -0.27613 -0.9996 [30] -0.9522 0.7175 [31] 0.9140 -- [32] 0.9110 0.062 0.720 [33] --0.848 [34] 0.9998 0.9992 -Proposed 0.8621 0.7925 -To validate the obtained results for the video 'engine.avi' are compared with the results of recently published state-of-art schemes [20,[31][32][33][34][35][36] that shows resilience under different attacks. Table 3 shows the results of comparison for several geometric attacks.…”
Section: Frame Averaging Outbreaksmentioning
confidence: 93%
“…The Table 2 shows that the sturdiness of the offered process is higher than the algorithms against several signal processing attacks mentioned by previous researchers. -0.27613 -0.9996 [30] -0.9522 0.7175 [31] 0.9140 -- [32] 0.9110 0.062 0.720 [33] --0.848 [34] 0.9998 0.9992 -Proposed 0.8621 0.7925 -To validate the obtained results for the video 'engine.avi' are compared with the results of recently published state-of-art schemes [20,[31][32][33][34][35][36] that shows resilience under different attacks. Table 3 shows the results of comparison for several geometric attacks.…”
Section: Frame Averaging Outbreaksmentioning
confidence: 93%
“…From the outset, the patient protects the information by encryption and uploads it to the BC. Rupa et al [6] suggested knowledge system made up of several parts: clients, specialists, users, expertise engineers, entered agents in addition to expert systems, inference agents, and intelligent agents. Knowledge engineering phases are considered when designing and implementing the suggested decentralized blockchain application (DApp) for official health record production and management.…”
Section: Related Workmentioning
confidence: 99%
“…By doing this, we will be able to create an ideal threshold and thus increase the accuracy for future diagnosis help. In order to extract some relevant elements and create an improved image, we have also used image processing, which can be used to conduct a variety of operations on the image [23,24]. When the input and the output are both images, a technique known as signal processing is performed.…”
Section: Proposed Solutionmentioning
confidence: 99%